KUALITAS PENGUNGKAPAN KEBERLANJUTAN GOTO GROUP DAN IMPLIKASI MANAJERIAL PADA PERUSAHAAN PLATFORM - Tandori Tandori; Annisatul Husna; Priya Swayanuar; Peter Johan; Lukas Purwoto; Antonius Sumarwan (Center for Economic Studies Universitas Katolik Parahyangan, 2026)
This article examines the quality of GoTo Group's sustainability disclosure and its managerial implications for platform firms. The research uses a qualitative document-based case study drawing on GoTo Group's Sustainability Reports for FY2022, FY2023, and FY2024, all of which were audited or externally verified, including verification by the Science-Based Targets Initiative for the FY2023 report. The analysis is structured around three indicators: measurability, verifiability, and information depth across environmental, social, and governance dimensions. The findings show that GoTo has developed a strong sustainability narrative, but the quality of its disclosure remains uneven. Environmental disclosure still relies heavily on relative metrics without sufficient absolute baselines. The carbon offset initiative (GoGreener) is not fully supported by clear information on fund allocation and independent verification. Social disclosure emphasizes inclusion and partner support, yet provides limited evidence on structural impacts on income stability and risk distribution. Governance disclosure also remains constrained by limited transparency regarding algorithmic mechanisms that are material to platform accountability. These findings suggest that sustainability disclosure in platform firms should be assessed not only by the strength of narrative communication, but also by the quality of indicators, the traceability of evidence, and the clarity of governance arrangements. The article's conceptual contribution lies in showing that sustainability legitimacy in platform firms depends on measurability, verifiability, and information depth as the basis for evaluating disclosure credibility.